Immunohistopathological Analysis of Immunoglobulin E-Positive Epidermal Dendritic Cells with House Dust Mite Antigens in Naturally Occurring Skin Lesions of Adult and Elderly Patients with Atopic Dermatitis - Ryoji Tanei; Yasuko Hasegawa (MDPI AG, 2021)
The immunopathogenic role of house dust mite (HDM) allergens in the development of skin lesions in atopic dermatitis (AD) has not yet been precisely clarified. We immunohistopathologically evaluated the localization of immunoglobulin E (IgE)-positive epidermal dendritic cells with HDM antigens in the skin lesions of patients with IgE-allergic AD. Using double-immunofluorescence and single-immunochemical staining methods, we analyzed biopsy specimens from the skin lesions of six patients with IgE-allergic AD and HDM allergy and 11 control subjects with inflammatory skin disorders. Inflammatory dendritic epidermal cells (IDECs; CD11c+ and CD206+ cells) were markedly observed in the central area of the spongiotic epidermis of skin lesions in all AD patients. Furthermore, IgE-positive IDECs with HDM antigens in the central areas of the spongiosis were found in four of the six (66.7%) AD patients. Langerhans cells (LCs; CD207+ cells) with HDM antigens were also observed in the peripheral areas of the spongiosis. Infiltration of CD4+ and CD8+ T cells in association with IgE-positive IDECs and LCs with HDM antigens was seen in the spongiotic epidermis. An IgE-mediated delayed-type hypersensitivity reaction, in combination with IgE-bearing dendritic cells, specific T cells, keratinocytes, and HDM antigens, may lead to spongiotic tissue formation in eczematous dermatitis in AD.